Stakeholders Perspective on Alert Village Preparedness in Ngronggo Village Kediri City - Yeni Muslicha Dwi Rahayu; Setyo Budi Susanto (Journal for Quality in Public Health, 2020)
Background: Village / Alert Village is a picture of a community that is aware, willing and able to prevent and overcome various health problems that occur in the community. Purpose: This research was conducted in Ngronggo Subdistrict, Kota Kediri Subdistrict, because the Kelurahan already has and runs a Kelurahan Health Center (Poskeskel). Lack of understanding related to the duties and functions related to the alert villages, especially to the stakeholders, has not yet dropped the latest regulations from the local government which underlie and regulate the development of the active alert villages. This study aims to explore the readiness of stakeholders in the active alert village program in terms of knowledge, roles and constraints on the standby village program in Ngronggo village. Methods: This research uses descriptive qualitative research method with purposive sampling because it is inductive and the results emphasize more meaning. Results: Active alert kelurahan are characterized by having a poskeskel (kelurahan health center) as a marker for the establishment or readiness of the kelurahan in improving public health. The geographical location of the poskeskel is evidence that the government, in this case, Ngronggo Village cares about the health status of its people. The cadre as an arm of the Ngronggo Village was able to provide education to the public about preventing an illness. The administration system is currently in the process of repairing and reworking so that the poskeskel function can be realized as a data bank. Conclusion: Village as the owner of the area also has an important role in the selection of resources. The puskesmas was able to advocate these regulations so as to clarify the tasks and roles of each individual involved in active alert kelurahan activities in Kelurahan Ngronggo.